Regulation of the Alternative Neural Transcriptome by ELAV/Hu RNA Binding Proteins - Wei, Lu; Lai, Eric C. (Frontiers in Genetics, 2022)
Numerous regulatory paradigms were initially recognized as oddities or exceptions, but were subsequently recognized as being implemented broadly. The process of alternative polyadenylation (APA), which generates multiple 3' UTR isoforms for a given locus, follows such a trajectory. APA was initially characterized for a few genes, but in the past decade, has been found to be the rule for metazoan genes. While numerous differences in APA profiles have been catalogued across genetic conditions, perturbations, and diseases, our knowledge of APA mechanisms and biology is far from complete. In this review, we highlight recent findings regarding the role of the conserved ELAV/Hu family of RNA binding proteins (RBPs) in generating the broad landscape of lengthened 3' UTRs that is characteristic of neurons. We relate this to their established roles in alternative splicing, and summarize ongoing directions that will further elucidate the molecular strategies for neural APA, the in vivo functions of ELAV/Hu RBPs, and the phenotypic consequences of these regulatory paradigms in neurons.